2019
DOI: 10.3171/2019.3.peds18624
|View full text |Cite
|
Sign up to set email alerts
|

Papilledema in unicoronal synostosis: a rare finding

Abstract: OBJECTIVEUnicoronal synostosis results in frontal plagiocephaly and is preferably treated before the patient is 1 year of age to prevent intracranial hypertension (ICH). However, data on the prevalence of ICH in these patients is currently lacking. This study aimed to establish the prevalence of preoperative and postoperative signs of ICH in a large cohort of patients with unicoronal synostosis and to test whether there is a correlation between papilledema and occipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…In the anatomic ophthalmic domain, papilledema was the most reported anomaly in both non-syndromic 1% (n = 333; 95% CI 0-18) [18,[20][21][22] and syndromic craniosynostosis 18% (n = 474; 95% [18,20,21,[25][26][27][28][29][30][31][32][33][34]. In non-syndromic craniosynostosis, only one study reported papilledema in lambdoid craniosynostosis, with a prevalence of 67% (n = 9) [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the anatomic ophthalmic domain, papilledema was the most reported anomaly in both non-syndromic 1% (n = 333; 95% CI 0-18) [18,[20][21][22] and syndromic craniosynostosis 18% (n = 474; 95% [18,20,21,[25][26][27][28][29][30][31][32][33][34]. In non-syndromic craniosynostosis, only one study reported papilledema in lambdoid craniosynostosis, with a prevalence of 67% (n = 9) [19].…”
Section: Discussionmentioning
confidence: 99%
“…All anatomical ophthalmic anomalies in non-syndromic craniosynostosis are sented in Table 2. Compared to syndromic craniosynostosis papilledema was less c mon in non-syndromic craniosynostosis, with a prevalence of 6% (n = 333; 95% CI 0 [18][19][20][21][22]. It had the highest prevalence in lambdoid craniosynostosis 67% (n = 9) repo Abbreviations: RS = Retrospective case study; CS = case-series; PS = prospective study; CFS = Craniofrontonasal dysplasia.…”
Section: Non-syndromic Craniosynostosismentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding unicoronal synostosis, a recent study by Van de Beeten found papilledema in 1 patient out of 89 (1.1%) in the postoperative follow-up trajectory for which no surgery was necessary. 41 Given this very low prevalence, screening in children with non-syndromic unicoronal synostosis does not seem to be of any value.…”
Section: Screening For Increased Icpmentioning
confidence: 99%